MCSA/MCSE self-paced training kit. - Holme, Dan (Microsoft Press, 2004)
The Readiness Review Suite powered by MeasureUp provides 850 challenging questions on CD for in-depth self-assessment and practice. You can choose timed or untimed testing mode, generate random tests, or focus on specific objectives. You get detailed explanations for right and wrong answers—including a customized learning path that describes how and where to focus your studies